Budget politics in the Philippines - Falguera, Norris Z. (Animo Repository, 2004)
This paper focuses on the separation of powers and purpose in the presidential system of government, and how these affect the budgetary process. The Executive is generally more inclined towards policies of national interests, while the Legislature is more inclined towards policies that target specific constituencies. While the role of the Department of Budget and Management (DBM) allows for the Executives’ dominance in the budgetary process, co-operation between the two branches of government is required. Thus the paper concludes that the Executive has to seek out and compromise with the Legislature in order to ensure success of its budgetary policies. This view contradicts a common perception in the Philippines that the Executive may ignore members of Congress, who are perceived as corrupt and parochial, in order to attain its budgetary objectives.